(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The purpose of this research is to know the concept Of specialized banks and their importance in supporting the banking and national activities by supporting the agricultural and industrial sectors and the loans they need and highlighting the types Of loans granted and their payments through the study of evaluating the financial performance Of specialized banks in Iraq for industrial and agricultural banks. Banks to the extent of contributing to the decision-making and corrective actions to address weaknesses and the exploitation of strengths. which would develop the financial performance of banks, which will reflect on the economic situation Of the country. In order to achieve this, the researchers relied on the use of the inductive method in order to form the theoretical framework for the research and compilation of the required data and Information. The sample of the research is a sample of the two banks (Industrial Bank and Agricultural Bank) for the period 2016-2014 The research was based on a main hypothesis that the failure to develop a strategic plan is achievable for the activity Of granting loans and in order to achieve profits in the banks sample research. A number of conclusions have been reached, the most important of which are the failure of the industrial and agricultural banks to support the two important sectors in the country (industrial sector and agricultural sector) Through the granting Of loans has been set conditions for the granting of loans and controls strictly. which hinders borrowers from borrowing by the specialized banks, The study also came out with a number of recommendations, including: the development of plans and strategies for the granting of bank loans accurately and carefully and verifiable for both banks